Inoculação de microrganismos promotores de crescimento na cultura da beterraba - Sousa, Maiara dos Santos (2022)
The use of growth-promoting microorganisms is presented as a sustainable alternative to agricultural production to increase the productivity of several crops. In this context, the objective of the present work was to study the effects of the application of different biological inputs, in the agronomic characteristics in the culture of beet (Beta vulgaris L.), inoculated via seed. The experiment was conducted at the Center for Biological Control and Protected Cultivation Prof. Dr. Mário César Lopes, belonging to the Experimental Stations Nucleus of the Agricultural Sciences Center of UNIOESTE, Marechal Cândido Rondon, PR, from June to September 2021. The experiment was carried out in a randomized block design with eight treatments and four replications. , with plots consisting of three plants. The cultivar studied was Tall Top Early Wonder. The treatments used were T1 = Bacillus megaterium (strain BRM-119) + Bacillus subtilis (strain BRM-2084); T2 = Bacillus subtilis + Bacillus megaterium + Bacillus thuringienses (strain BRM-116); T3 = Azospirillum brasilense (AbV5 + AbV6 strains); T4 = Azospirillum brasilense (strain HM0-53); T5 = Azospirillum brasilense (strain HM-210); T6 = Pseudomonas fluorescens (strain ATCC-13525) and T7 = Thichorderma harzianum – (strain CCT7589) and T8 = control. Plant height, SPAD index, tuberous root diameter, tuberous root length, presence of rings, root shape index, tuberous root fresh mass, tuberous root dry mass, number of leaves, leaf area, shoot fresh mass, shoot dry mass , anthocyanin and carotenoid content. Plant height and SPAD index were evaluated at 60 and 85 DAS and the other evaluations were performed at the end of the cycle at 85 DAS. Inoculation of beet seeds with A. brasilense (strain HM-210) provided an increase in plant height, SPAD index, root diameter, root length, tuberous root fresh mass. The highest fresh mass of tuberous root was observed in the treatment with A. brasilense (strain HM-210) with an average mass of 321.63 g, not differing from the treatments with A. brasilenses (strains AbV5 + AbV6) (279 g) and T harzianum obtaining as results (285.65 g). Beetroot inoculated with P fluorensces had higher root dry mass (44.41 g), however they did not differ from those inoculated with A. Brasilenses. The fresh mass of the aerial part showed a difference between the treatments, promoting an increase in those in which the seeds were inoculated with B. megaterium (strain BRM-119) + B. subtilis (strain BRM-2084) and P. fluorescens (strain ATCC-13525) , differing only from the treatment B. subtilis + B. megaterium + B. thuringienses (strain BRM-116). The highest anthocyanin content (45.56 mg 100 g-1) was observed in the inoculation of B. megaterium + B. subtilis, differing from the treatments inoculated with B. subtilis + B. megaterium + B. thuringienses (strain BRM-116) , Azospirillum brasilense (strains AbV5 + AbV6), A. brasilense (strain HM0-53) and A. brasilense (strain HM-210). The inoculation of A. brasilense (strain HM-210) via seed in the beet crop allows a greater fresh mass of the root before the end of the crop cycle, in this way, this microorganism can be used to anticipate the harvest of the tuber.